Carbon and cellulose based nanofillers reinforcement to strengthen carbon fiber-epoxy composites: Processing, characterizations, and applications - Biswas, Pias Kumar; Omole, Oluwaseun; Peterson, Garrett; Cumbo, Eric; Agarwal, Mangilal; Dalir, Hamid (Frontiers in Materials, 2023)
Since the inception of carbon fiber reinforced polymer (CFRP) composites, different nanofillers have been investigated to strengthen their mechanical and physical properties. To date, the majority of research has focused on enhancing fiber/matrix interface characteristics and/or optimizing nanofiller dispersion within the matrix, both of which improve the performance of carbon fiber-epoxy composite structures. Nanofillers can be dispersed into the polymer matrix by different techniques or nanofillers are chemically bonded to fiber, polymer, or both via multiple reaction steps. However, a few studies were conducted showing the effects of different nanofillers on the performance of carbon fiber-epoxy composites. Here a critical study has been done to explore different nanofillers used to enhance the mechanical and physical properties of carbon fiber-epoxy composites. After giving a short history of carbon fiber production, the synthesis of nanofillers, dispersion in the polymer matrix, and chemical/physical bonding with the fiber or polymer have been extensively described here along with their processing techniques, characterizations, and applications in various fields.